Conceptual framework for an advertising balanced scorecard : case of the mobile network communication industry in South Africa - Ayingono Moussavou, Sandra (Stellenbosch : Stellenbosch University, 2009)
Thesis (MComm (Business Management))--Stellenbosch University, 2008.